New Polymer Syntheses Part: 55#. Novel Conducting Arylidene Polymers and Copolymers Based on Methyl-Cyclohexanone Moiety - Aly, K. I.; Hussein, M. A.; Al-Muaikel, N. S.; Zeid, E. Abo (Journal of Research Updates in Polymer Science, 2014)
A new interesting class of conducting polymers based on methyl-cyclohexanone in the polymer main chain has been synthesized by solution polycondensation of terephthalaldehyde with methyl-cyclohexanone. Copolymers containing different cycloalkanone moieties were also synthesized using solution polycondensation technique. The model compound I was synthesized by the interaction of methyl-cyclohexanone monomer with benzaldehyde, and its structure was confirmed by elemental and spectral analyses. The resulting new polymers and copolymers were characterized by elemental and spectral analyses, beside solubility and viscometry measurements. The thermal properties of those polymer and copolymers were evaluated by TGA, DrTGA and DTA measurements and correlated to their structural units. PDT as well as T10 was in the range from 205 to 370 ºC. In addition, T10 thermal stability for all the polymers was in the order: VI> II > III > IV > V. X– ray analysis showed that it has some degree of crystallinity in the region 2q = 5 – 60 degree.The UV– visible spectra of some selected polymers were measured in DMSO solution and showed absorption bands in the range 265-397 nm, due to n – p* and p – p* transition. The morphological properties of copolymer IV as selected examples were tested by SEM. The electrical conductivities of the synthesized polymers and copolymers enhanced to become in the range of 10-9-10-8 S cm-1 by doping with iodine.